Assessment of kisan sarathi in influencing farmers’ knowledge on rabi crop practices: A difference-in-difference (DID) approach - MUKHERJEE, SWEETY; PADARIA, RABINDRA NATH; BURMAN, RAJARSHI ROY; NIKAM, VINAYAK R; AISWARYA, S; MAHRA, GIRIJESH SINGH; ADITYA, KAUSTAV; KUMAR, AMRENDER; SAINI, SUSHMITA; MALLICK, SONALI; GORAI, SUDIP KUMAR (The Indian Journal of Agricultural Sciences, 2026)
Digital extension platforms have emerged as an important means of strengthening last-mile information delivery in Indian agriculture. Kisan Sarathi, a multimodal and interactive ICT-based advisory system, provides personalised and location-specific recommendations to farmers through Krishi Vigyan Kendras (KVKs). However, empirical evidence on its effectiveness in enhancing farmers’ knowledge remains limited. The present study, conducted during 2024–25, evaluates the contribution of Kisan Sarathi advisories in improving farmers’ knowledge of Rabi crop practices using a difference-in-difference (DID) approach. Uttar Pradesh was selected purposively due to its high registration on Kisan Sarathi and extensive area under major Rabi crops. A total of 300 farmers were surveyed from three districts selected through a stratified two-stage sampling method, comprising equal numbers of users and non-users. A standardised knowledge test was developed through item collection, expert validation and item analysis, yielding 17 items that were used for pre- and post-intervention assessments. The DID regression model with cluster-robust standard errors was applied to isolate the causal effect of the advisories. The results showed a significant rise in knowledge scores among Kisan Sarathi users compared to non-users, with the post-intervention experimental group coefficient (β = 4.36, p < 0.001) confirming a strong positive effect. Model diagnostics indicated robustness and moderate explanatory power. The findings demonstrate that Kisan Sarathi substantially enhanced farmers’ knowledge by delivering timely and need-based advisories. The study concludes that digital extension platforms like Kisan Sarathi can play a significant role in bridging information gaps and improving informed decision-making in agriculture, reinforcing their importance in future extension strategies.